Foreword: The 1st CETAPS Meeting on Digital Humanities - Luciano Moreira (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
Foreword to The 1st CETAPS Meeting on Digital Humanities